Implementation of the Criminal System for Children as Perpetrators of Criminal Acts from the Perspective of Law Number 11 of 2012 concerning the Criminal Justice System for Children - Jingga, Anya Jibril Ratu; Hapsari, Maharani Dwi; Hosnah, Asmak Ul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper explains the basis of legal protection for children who commit crimes according to the Republic of Indonesia Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which refers to the Convention on the Rights of the Child. The problems discussed also refer to the protection of children as perpetrators. The research method applied for this study is normative legal research, which is included in the realm of legal dogmatics and focuses on the analysis or study of legal regulations. This study, first, found that the provisions of punishment for children are in accordance with those regulated in Law Number 35 of 2014 which amends Law Number 23 of 2002 concerning Child Protection, which states that imprisonment may be imposed on children only if there is no other alternative, and must be separated from adult prisons. Second, efforts to protect children are carried out through the application of restorative punishment and diversion, if they meet the requirements stipulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.